Penerapan Prinsip Ekonomi Syariah Dalam Pemberian Modal Usaha Oleh BUMG Suak Raya - Asra Febriani; Putri Rahmayana (Seutia Hukamaa Cendekia, 2023)
BUMG is one of the efforts to improve the economy of rural communities. BUMG Suak Raya provides business capital loans to micro-entrepreneurs in Gampong Suak Raya. As Aceh is an area that applies Sharia principles, all aspects of life must be carried out by Islamic law. Writing this article aims to discover the application of Sharia economic principles in providing business capital to the community carried out by BUMG Gampong Suak Raya and the challenges BUMG Gampong Suak Raya faces in providing venture capital to the community. This research is qualitative field research, and data collection techniques were carried out by interviews, observation, documentation, and data analysis using descriptive analysis techniques. Based on the results of the study, it can be concluded that the application of Sharia principles in the distribution of business capital loans by BUMG Suak Raya is providing business capital loans to micro-entrepreneurs by BUMG Gampong Suak Raya as a form of helping the household economy and interest-free loans. The challenge faced in channeling business capital loans from BUMG Suak Raya to the community is that some members are not trustworthy, and BUMG Suak Raya obtains no benefits, so BUMG Suak Raya is difficult to develop.